2016
DOI: 10.1055/s-0035-1571141
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology Profile of Traumatic Spine Injury of a Spinal Cord Service in the State of Espírito Santo

Abstract: Objective To analyze the epidemiological profile of patients with traumatic spinal cord injury (SCI) undergoing surgical procedures in the state of Espírito Santo, Brazil. Methods A cross-sectional, descriptive study was performed based on the analysis of 70 medical records of patients who underwent surgery due to traumatic SCI in the state of Espírito Santo, Brazil. Results Males comprised 79% of the patients. The average age of the occurrence of the traumatic SCI was 44 years; automobile accidents were the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
4
1
1
Order By: Relevance
“…Thus, we can say that men more likely to suffer from spine injuries. 3 , 18 On the other hand, although the mean age of trauma patients with spine injury in Brazil, the United States, Germany, Japan, and Italy varied between 44 and 60 years 10 , 20 , 21 , 22 , 23 and estimated to be 40 years in the world, 3 in the present study the mean age of spine injury victims was 38 years. Therefore, since traumatic injuries are 1 of the main causes of disability, especially among young people, which has a great impact on the years of life with disability, 24 it is necessary to pay attention to preventive measures focusing on young men.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Thus, we can say that men more likely to suffer from spine injuries. 3 , 18 On the other hand, although the mean age of trauma patients with spine injury in Brazil, the United States, Germany, Japan, and Italy varied between 44 and 60 years 10 , 20 , 21 , 22 , 23 and estimated to be 40 years in the world, 3 in the present study the mean age of spine injury victims was 38 years. Therefore, since traumatic injuries are 1 of the main causes of disability, especially among young people, which has a great impact on the years of life with disability, 24 it is necessary to pay attention to preventive measures focusing on young men.…”
Section: Discussioncontrasting
confidence: 52%
“… 3 And in 2017, motor vehicle accidents and falls were the most common causes of spine injury worldwide. 18 Other researchers in their studies in different countries showed that traffic accidents 10 , 20 , falls and road injuries 25 , falls and collisions of motor vehicles 26 , falls (57.1%) and transport accidents (19.9%) 27 , car accident (44.0%), 21 motor vehicle accident (29.3%), and fall (23.7%) 22 , 23 were cited as the most common cause of spine cord trauma. Car accidents and falls were major causes of traumatic spinal injuries, given the preventable nature, health planners and managers should review traumatic injury trends and identify at-risk groups to implement targeted prevention policies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to physical, mental and social limitations, the injury is responsible for a considerable financial impact both for the victim and for the public or private healthcare system. To elucidate this impact, it is estimated in the United States a cumulative cost of 1.1 to 4.6 million dollars per patient, including costs for hospital expenses, treatment and lost productivity, considering that the most affected group is in an age group of high labor productivity (Roberts et al, 2017;Scopel et al, 2018;Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%